CTX-M-9 group ESBL-producing Raoultella planticola nosocomial infection: first report from sub-Saharan Africa - Tafese Beyene Tufa; Andre Fuchs; Torsten Feldt; Desalegn Tadesse Galata; Colin R. Mackenzie; Klaus Pfeffer; Dieter Häussinger (Annals of Clinical Microbiology and Antimicrobials, 2020)
Abstract Background Raoultella are Gram-negative rod-shaped aerobic bacteria which grow in water and soil. They mostly cause nosocomial infections associated with surgical procedures. This case study is the first report of a Raoultella infection in Africa. Case presentation We report a case of a surgical site infection (SSI) caused by Raoultella planticola which developed after caesarean section (CS) and surgery for secondary small bowel obstruction. The patient became febrile with neutrophilia (19,157/µL) 4 days after laparotomy and started to develop clinical signs of a SSI on the 8th day after laparotomy. The patient continued to be febrile and became critically ill despite empirical treatment with ceftriaxone and vancomycin. Raoultella species with extended antimicrobial resistance (AMR) carrying the CTX-M-9 β-lactamase was isolated from the wound discharge. Considering the antimicrobial susceptibility test, ceftriaxone was replaced by ceftazidime. The patient recovered and could be discharged on day 29 after CS. Conclusions Raoultella planticola was isolated from an infected surgical site after repeated abdominal surgery. Due to the infection the patient’s stay in the hospital was prolonged for a total of 4 weeks. It is noted that patients undergoing surgical and prolonged inpatient treatment are at risk for infections caused by Raoultella. The development of a SSI caused by Raoultella planticola with extended AMR has to be assumed to be a consequence of ineffective antibiotic utilization. The presented case advices that rare bacteria as Raoultella should be considered as potential cause of nosocomial SSI with challenging treatment due to high levels of AMR.